The Effectiveness of the Multisensory Approach on Students’ Vocabulary Mastery at SMAN 2 Sukawati - Ketut Ayu Swandewi; I Putu Andre Suhardiana; I Dewa Gede Rat Dwiyana Putra (Educational Journal, 2026)
This study aimed to examine the effectiveness of multisensory approach on eleventh-grade students’ vocabulary mastery at SMA N 2 Sukawati and to investigate students’ perception of its implementation. This study employed quantitative research method with a quasi-experimental research design involving 68 eleventh-grade students. Test and questionnaires were used to collect the data, which were analyzed using descriptive and inferential statistical analyses. The finding revealed a significant difference in the post-test results between experimental and control groups after controlling the pre-test results as the covariate, F (1,65) = 4.666, p = 0.034, ηp2 = 0.067. In addition, the questionnaire results showed the mean scores ranging from 3.00 to 4.71, indicating that the multisensory approach positively affected students’ vocabulary mastery and generated positive perceptions toward vocabulary learning. However, this study was limited by the small number of participants and short duration of the research. Future researchers are encouraged to conduct the similar studies with larger samples of participants and longer research duration to obtain more comprehensive findings.